(untitled) (Journal of the College of Basic Education, 2023)
The explanations are linguistic boundaries, structures, and styles of Arabic poetry that found their way in the hands of linguists, critics, and grammarians. Until they demolished its building in order to rearrange it with authentic Arabic styles, known to the world’s linguists only in the last century; While its features were drawn by Ibn al-Anbari with religious, historical and psychological trends, and it reached the peak of its maturity in the hands of al-Marzouqi by constructing words and meanings of readings and inclinations and the juxtaposition of words to generate new meanings, as well as the departure of compositions from grammatical analogy in accordance with the habit of eloquent Arab poets in borrowing buildings for meanings; The measure of the eloquence of all of this is based on the words of the Qur’an.It is one of the peaks of the grammatical lessons that broke the stagnation and dryness of the rule with the delicacy of poetic taste in its meanings that included all the structures of the language.